Maternal complications in twin pregnancy; recent trends: a study at a tertiary care referral institute in Northern India - Dubey, Sunita; Mehra, Reeti; Goel, Poonam; Rani, Jyotsna; Satodiya, Mohit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study aims to determine the maternal complications in twin pregnancy in North Indian population at tertiary institute. Methods: This was a retrospective cohort review of multiple pregnancies after 20 weeks gestation at a tertiary teaching hospital (2011-2015). Maternal data was collected from the labor room delivery data entry register and patient’s admission file. Patients with diabetes mellitus and chronic hypertension were excluded from the study. Results: Out of 19539 births during this period, 432 were twin pregnancies with an incidence of 22/1000 birth. Most of them were 282 (65.4%) were referred patients. Eighty seven percent patients were in the age group of 21-30 years and primigravida contributed to 45.7% of total patients. Maternal complications noticed were as preterm deliveries in 304 (70%), anaemia in 259(60%) patients, preterm rupture of membranes in 120 (39.4%) patients, hypertensive disorders of pregnancy in 122(28.3%) patients, cholestasis of pregnancy in 24(5.5%) of patients, hypothyroidism in 22(5.1%) of patients, antepartum hemorrhage (APH) in 20(4.6%) and gestational diabetes mallitus (GDM) in 08(1.8%) of patients. Among postpartum complications, atonic postpartum haemorrhage (PPH) was observed in 44 (10.2%) and maternal mortality happened in 02(0.46%) cases. Conclusions: This study reveals higher percentage of, preterm labor, anaemia, and gestational hypertension than other studies. More number of intensive care unit should be established in high prevalence areas to prevent perinatal mortality due to prematurity. Treatment of anaemia requires more aggressive approach by considering intravenous iron whenever compliance is in doubt. Frequent antenatal care is required for early diagnosis of these complications to prevent maternal and fetal morbidity.